ANALISIS TEKS BACAAN DALAM WEBSITE ISL COLLECTIVE DEUTSCH SEBAGAI BAHAN AJAR PEMBELAJARAN KETERAMPILAN MEMBACA BAHASA JERMAN SISWA SMA KELAS XI - PARAMITA, MUTHIA (LATERNE, 2016)
There In foreign language learning, the skills of reading is a skill that must be mastered by students. Students are expected to understand the different types of readings and a range of text that they meets. With the development of technology that is getting increasingly sophisticated day has given the ease to acquire a wide range of reading text to suit your needs. One of them is through the internet. In the internet, the teachers can share the learning material through file-sharing sites to do through online teaching and learning activities. From the large number of existing learning site, ISL Collective is one of the Germany language learning site that can be used as source materials. But the material contained in the site are still not can be called a proper learning materials because there are several conditions that must be adjusted to the rules and also with the existing curriculum. Therefore need to do an analysis of the existing material by taking six samples from the website that is already customized with subtema which taught to students so they can be ascertained for compliance with curriculum 2013 as Germany language learning materials high school students of 11th Grade. Outline of the problems from this research is whether that six texts can be used as learning materials Germany language learning skill in reading high school students of 11th grade or not. Whereas the aim of this research is to know the appropriateness of text readingsin Collective ISL website (Deutsch) as Germany language learning materials in the reading skills of high school students of 11th grade. This research is a descriptive qualitative research by conducting an analysis of the data. This data is in the form of six texts and reserved the exercise you selected fit the themes of teaching and learning materials according to Prastowo’s criteria of learning material. Next, it will be matched to map a predefinedmaterial by 2013 and curriculum theory level understanding of Bloom. Conclusion of this research is all the text in the website meets the standards of competence in the curriculum of 2013, as well as reach the indicator reading should at least there arevocabulary, phrases, and sentence patterns komunik atif according theme, based onkeywords, pictures, floor plans, or charts that have been provided. In addition, based on the theory of the comprehension level of Bloom, five of the six are already reached a level of understanding (C2). While the text reading